LEGAL REVIEW OF THE READINESS OF BUSINESS IMPLEMENTATION BASED ON HUMAN RIGHTS IN THE MAKASSAR INDUSTRIAL AREA - Arman Muis; Teguh Prasetyo; Elvira Fitriyani Pakpahan; Alkana Yudha; Vita Cita Emia Tarigan; M. Iqbal Asnawi (Fakultas Hukum, Universitas Samudra, 2024)
The position of business actors in today's development has a significant impact on the economic sector of a country. On the other hand, business activities can have an impact on social change, considering that the business activities of business actors have a direct impact on society and the environment, and have the potential for human rights violations. Makassar Industrial Estate is one of the icons of economic growth and the centre of business activities in eastern Indonesia, which has intersections with human rights in the implementation of its business activities. This research uses the type and form of normative legal research that examines and analyses based on legal theories, legal principles and things written in laws and regulations (law in book) as well as legal literature to answer problem issues. The research method uses a conceptual approach and a statutory approach. The technique used to collect legal material is a literature study document study. The results show that since the establishment of the United Nations (UN), the issue of human rights has emerged and become a serious discussion in every international forum. Since 2005, human rights issues have become more focused on the business sector. As a member of the UN, Indonesia has committed to focus on business and human rights by issuing Presidential Regulation No. 60 of 2023 on the National Strategy for Business and Human Rights in 2023. Business activities in the Makassar Industrial Estate still have a negative record on environmental issues and child labour, which is one of the business and human rights issues. Legal and institutional readiness is needed to implement Indonesia's commitment to focus on human rights-based business.